Single-Switch Soft-Switched Boost Power Factor Corrector for Modular Applications - Tomas A. Gonzalez; Daniel O. Mercuri; Hernan E. Tacca; Maximo E. Pupareli (Institute of Advanced Engineering and Science, 2016)
Modern dc power supplies provide power factor correction but the classical two-stage approach, using hard-switched preregulators, has detrimental effects on efficiency and reliability, particularly for high power applications. With some circuit modifications and the addition of a few magnetic components, diodes and capacitors, we have turned a classical boost power factor corrector into a high efficiency soft-switched version. The proposed converter turns on its single switch with zero current and turns it off with zero voltage. In this paper we explain the proposed changes, we study the waveforms and equations and we verify them with an experimental prototype. We also show how the converter can be used for modular single- and three-phase high power applications.